Efektivitas Model Pembelajaran Scientific Inquiry Berbasis Kearifan Lokal Budaya Melayu terhadap Minat Belajar Mahasiswa - Putrini R Harahap, Saima (CV. Pusdikra Mitra Jaya, 2024)
The aim to be achieved through research is to see the effect of implementing the Malay Culture-based scientific inquiry learning model on increasing student interest in learning. This study employed a quantitative approach and included 55 students in their third semester, divided into two sample groups. The experimental class (Class A) consisted of 27 students, while the control class (Class B) comprised 28 students.. This research was conducted in the context of the Hydrology course. Data was collected through tests and analyzed using IBM SPSS 23. After implementing the scientific inquiry learning model based on Malay culture and conventional learning, the average pretest score for student interest in learning in the experimental class was 59.77 and after being given treatment using the scientific inquiry learning model, The student's posttest score was 80.55. The results of the independent sample-test showed a significant value of 0.000, where the value was <0.05. Thus, it can be deduced that the use of the Malay Culture-based scientific inquiry learning model has a positive impact in increasing students' interest in learning.